When my bike flies and other stories - "Horsburgh, Nicholas" (Oxford University Press: Karachi, 2022)
When My Bike Flies and Other Stories is part of the Oxford Reading Treasure series, authored by Nicholas Horsburgh. This collection is designed for children aged 6 to 10, aiming to instill a love for reading while enhancing fluency and comprehension. Each book in the series contains four to six independent stories, featuring tales of laughter, adventure, fantasy, and real-life scenarios. The series is structured across five graded levels, with three books per level, each incorporating vocabulary lists to support language development.
Keywords: adventure, fantasy